Menakar Ulang Kedudukan TAP MPR dalam Konstelasi Peraturan Perundang Undangan Pasca Amandemen - Nur, Fadlah; Nabilla Syifa Auliya; Siti Zahra (Jurnal Restorasi Hukum, 2025)
The amendment of the Constitution does not only change the authority and position of the MPR in the constitutional system but also has an impact on its legal products. The placement of MPR Decree in the hierarchy of laws and regulations raises norm conflicts that lead to legal uncertainty, this research aims to examine how the ideal position of MPR Decree in the hierarchy of laws and regulations. This research uses normative juridical method with conceptual approach and statute approach. The results of the study found that there are several norm conflicts due to the inclusion of TAP MPR in the hierarchy, namely the issue of content material, the role of the consideration, the status of validity and constitutional testing which causes legal uncertaint. The author offers two alternative recommendation to the legislators. First, it is necessary to reassess to determine which provisions are still relevant to be maintained, so that a definite number is agreed upon. Then the content material is moved into the law. So that all MPR Decrees can still be used in the form of laws. Then revise the hierarchy of laws and regulations. Secondly, the lawmakers can just leave the MPR Decrees that are still recognised as MPR Decrees, with the legal status of laws and regulations. Whatever the lawmakers' choice, the MPR Decree must be removed from the hierarchy. Amandemen Undang Undang Dasar  tidak hanya mengubah wewenang dan kedudukan MPR dalam sistem ketatanegaraan namun juga berimbas pada produk hukum nya. Penempatan TAP MPR dalam hierarki peraturan perundang undangan menimbulkan konflik norma yang berujung pada ketidakpastian hukum, penelitian ini bertujuan untuk mengkaji bagaimana idealnya kedudukan TAP MPR dalam hirrarki  peraturan perundang undangan. Penelitian ini menggunakan  metode yuridis normatif dengan pendekatan konseptual. Pengumpulan data yang digunakan dalam penelitian ini menggunakan kajian literatur . hasil penelitian menemukan terdapat beberapa konflik norma karena masuknya TAP MPR dalam hierarki yaitu masalah materi muatan, peran konsideran, status keberlakuan dan pengujian konstitusional yang menimbulkan ketidakpastian hukum sehingga TAP MPR harus dikeluarkan dari hierarki melalui revisi UU no.12/2011